Annual personalised calculator for prognostication after ST-segment elevation myocardial infarction - V. B. Barbarich; N. G. Lozhkina; A. A. Tolmacheva; M. H. Hasanova; E. A. Stafeeva; I. Mukaramov; O. M. Parhomenko; A. D. Kuimov; Ju. E. Voskobojnikov (Фундаментальная и клиническая медицина)
Aim. To create a calculator for the annual personalised risk assessment of adverse cardiovascular events in patients after acute ST-segment elevation myocardial infarction (STEMI).Materials and Methods. Here we performed a prospective data analysis of 1,000 patients diagnosed with STEMI during 2017 and 2018 and admitted to Regional Vascular Center. For evaluating the risk of adverse cardiovascular events after STEMI, we applied the GRACE scale. After 1 year of follow-up, the predicted outcomes were compared with the actual outcomes. We then created a personalised calculator of unfavorable outcome by using logistic regression.Results. The calculator included six indicators that significantly correlated with outcomes and poorly correlated with each other: left ventricular ejection fraction (LVEF) < 40%, anterior STEMI, tachycardia upon admission, fasting blood glucose, high-sensitive C-reactive protein (CRP), and patient age.Conclusion. We found a high reliability of our calculator for the annual personalised prognosis of adverse outcome in patients after STEMI.